1974
DOI: 10.1007/bf01039793
|View full text |Cite
|
Sign up to set email alerts
|

Simulation of germination of winter annuals in relation to microclimate and microdistribution

Abstract: A simulation program on the germination of winter annuals is written in such a way that the influence of changing environmental conditions on germination characteristics such as the time of germination, the percentage of germination and the distribution function of germination is described as well as possible in accordance with experimental data. The changing environmental conditions are simulated by a program that describes the changes of the microclimatological characteristics, temperature and moisture conte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

1976
1976
1985
1985

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 19 publications
0
5
0
Order By: Relevance
“…In winter annuals, summer seed dormancy appears to be an adaptation which prevents germination during temporary moist periods in summer and thus allows the species to persist in hot, dry summer habitats (Ratcliffe, 1961;Newman, 1963;Thompson, 1970;Baskin and Baskin, 1971a;Hajkova and Krekule, 1972;Janssen, 1974). However, very little information is available concerning the effect of temperature on afterripening of the seeds.…”
Section: Introductionmentioning
confidence: 99%
“…In winter annuals, summer seed dormancy appears to be an adaptation which prevents germination during temporary moist periods in summer and thus allows the species to persist in hot, dry summer habitats (Ratcliffe, 1961;Newman, 1963;Thompson, 1970;Baskin and Baskin, 1971a;Hajkova and Krekule, 1972;Janssen, 1974). However, very little information is available concerning the effect of temperature on afterripening of the seeds.…”
Section: Introductionmentioning
confidence: 99%
“…Many authors have devised indices of speed of germination to allow comparisons between populations (e.g.. Tucker & Wright 1965;Nichols & Heydecker 1968;Goodchild & Walker 1971;Janssen 1973). In the studies reported in this paper, the speed of germination is expressed as 'the percentage of non-dormant seed germinating in 12 h'.…”
Section: Methods and Resultsmentioning
confidence: 97%
“…Yet another method for obtaining complex relationships is the use of a "black box" which simulates the relation between input and output, Janssen (1974) has used it in his model of germinating seeds of winter annuals. 19 All three methods described can be combined with statistical methods or the accuracy of the results can be compared with independently measured values.…”
Section: Evaluation Of Modelsmentioning
confidence: 99%